An overview: Fatigue behaviour of ultrafine-grained metals and alloys - Höppel, Heinz Werner; Kautz, Martin; Xu, Cheng; Murashkin, Maxim; Langdon, Terence G.; Valiev, R. Z.; Mughrabi, Hael (International Journal of Fatigue, 2006)
The objectives of the present study were to assess and to optimize the fatigue behaviour in strain-controlled tests of different ultrafine-grained (UFG) metals and alloys (Cu, Al, AA6061, α-brass) prepared by equal channel angular pressing (ECAP). Quite generally, the UFG materials investigated exhibited shorter fatigue lives in the low-cycle fatigue (LCF) regime than corresponding conventional grain (CG) size specimens. In all cases, the fatigue lives could be enhanced appreciably by a suitable heat treatment following ECAP without, however, paralleling the fatigue lives of the CG specimens. The microstructural reasons for this behaviour are discussed, and a microstructure-based fatigue life model for UFG materials is presented.
Created from Fastlane, Scopus look-up
Keywords: α-Brass; AA6061; Aluminium; Annealing; Copper; ECAP; Fatigue life; Modelling; Ultrafine-grained materials